2016
DOI: 10.1021/jacs.5b12589
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Marine Glycosphingolipid Vesparioside B

Abstract: The first total synthesis of a major component of marine glycolipid vesparioside B ( Scheme 1 , 1, R1 = n-C22H45, R2 = n-C14H29) has been accomplished through a convergent [4 + 3] coupling strategy. Key steps included stereoselective installment of a set of challenging 1,2-cis-glycoside bonds. A 2-quinolinecarbonyl-assisted α-galactosylation and a novel β-arabinosylation were developed, respectively, to synthesize the α-galactofuranosidic and the β-arabinopyranosidic linkages. Furthermore, a 4,6-O-benzylidene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 55 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…The preparation of synthons 2 , 3 b , and 5 was carried out as illustrated in Scheme . The synthesis of the Gal f thioglycoside 2 began with the known ethyl β‐D‐thio‐galactofuranoside ( 6 ) . This compound was easily converted into 5,6‐diol 7 in 82% yield over three steps: protection of 5,6‐OHs as a isopropylidene acetal, di‐ p ‐methoxybenzylation at C2 and C3 positions, and deprotection of the 5,6‐ O ‐isopropylidene group.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of synthons 2 , 3 b , and 5 was carried out as illustrated in Scheme . The synthesis of the Gal f thioglycoside 2 began with the known ethyl β‐D‐thio‐galactofuranoside ( 6 ) . This compound was easily converted into 5,6‐diol 7 in 82% yield over three steps: protection of 5,6‐OHs as a isopropylidene acetal, di‐ p ‐methoxybenzylation at C2 and C3 positions, and deprotection of the 5,6‐ O ‐isopropylidene group.…”
Section: Resultsmentioning
confidence: 99%
“…The yield could be improved with use of the acetyl protecting groups ( 22 : 84 %). The diacetyl l ‐arabinose was compatible with a C4 hydroxy group to afford α‐ 23 . A similar trend was observed with d ‐arabinose ( 24 – 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…[9] Recently, Monteiro et al demonstrated the potentialo faLPS-based vaccine against H. pylori,i nw hich the conserved core undecasaccharide [9b, 10] 1 (Figure 1) wasi dentified as ap romising antigen for the development of ag lycoconjugate vaccine targeting all strains. [13] Convergent strategies can focus either on a[ 4 + +4] or a[ 3 + +5] key coupling. [11d, 12] The outer core octasaccharide portion of core undecasaccharide 1 is the key synthetic target.…”
mentioning
confidence: 99%